Investigação epidemiológica e molecular da infecção pelo vírus da hepatite C em usuários de drogas ilícitas no Brasil Central - LOPES, Carmen Luci Rodrigues (2009)
Hepatitis C virus (HCV) infection is an important problem of public health. Drug users (DU) constitute a group of frequent exposure to HCV and little is known about this infection in DU in Brazil. This study aimed to investigate the seroepidemiological and molecular profile of HCV infection among drug users in Central Brazil. A total of 691 DU, being 102 injection drug users (IDU) and 589 noninjecting drug users (NIDU), were interviewed and blood samples collected in 26 treatment drug centers in Campo Grande-MS and Goiânia-GO. Blood samples (sera) were tested for antibodies to HCV (anti-HCV). Anti-HCV-positive samples were submitted to HCV RNA detection by polymerase chain reaction (PCR) with primers complementary to the 5 NC and NS5B regions of viral genome and genotyped by LiPA and direct nucleotide sequencing followed by phylogenetic analysis, respectively. The anti-HCV prevalence was 6.9% (95% CI: 5.2-9.2). The study population reported a low known regarding HCV transmission ways, such as parenteral (20.8-30.5%), sexual (31,7%) and vertical (20%) of HCV. Multivariate analysis of risk factors revealed that age > 40 years, route (injecting) and duration of drug use and blood transfusion were associated with HCV infection. HCV RNA was detected in 85.4% of the anti-HCV-positive samples. Thirty-three samples were of genotype 1 by the LiPA, subtypes 1a (63.4%) and 1b (17.1%), and eight samples (19.5%) were of genotype 3, subtype 3a. The phylogenetic analysis of the NS5B region showed that 17 (68%), 5 (20%) and 3 (12%) samples were of subtypes 1a, 3a and 1b, respectively. This study shows a high HCV infection prevalence and the predominance of subtype 1a among drug users in Central Brazil. Also, the injecting drug use was the risk factor most strongly associated with this infection. In addition, the study population reported a low known regarding HCV transmission ways. Thus, preventive measures are needed to control this infection in illicit drug users